2017
DOI: 10.1111/bjhp.12267
|View full text |Cite
|
Sign up to set email alerts
|

‘It's like a frog leaping about in your chest’: Illness and treatment perceptions in persistent atrial fibrillation

Abstract: Objectives. Persistent atrial fibrillation (AF) is an abnormal heart rhythm associated with low quality of life (QoL) and significant health-related costs. The purpose of the study was to examine patients' illness and treatment beliefs and ways of coping with AF symptoms, to provide insight into promoting better QoL and treatment-specific management.Design. Beliefs were explored across three procedural treatment groups using a qualitative cross-sectional design.Methods. Thirty semi-structured interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 36 publications
0
40
0
1
Order By: Relevance
“…58 This is supported in AF patients by a qualitative study which reported AF patients' difficulty in identifying the benefits of individual treatments. 15 Poor knowledge of the necessity for warfarin is well documented; One study found that a majority of patients were unable to name one risk or benefit of warfarin or the reason for taking it. 59 A previous intervention in AF patients, which focused on improving understanding of warfarin and reducing perceptions of harm, significantly improved adherence and time spent in the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 This is supported in AF patients by a qualitative study which reported AF patients' difficulty in identifying the benefits of individual treatments. 15 Poor knowledge of the necessity for warfarin is well documented; One study found that a majority of patients were unable to name one risk or benefit of warfarin or the reason for taking it. 59 A previous intervention in AF patients, which focused on improving understanding of warfarin and reducing perceptions of harm, significantly improved adherence and time spent in the therapeutic range.…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study suggested patients have negative perceptions about the potential harm of anticoagulants, but not antiarrhythmics. 15 Negative beliefs about anticoagulants may arise as vitamin-k antagonists, such as warfarin, require frequent INR monitoring to ensure patients are within therapeutic range (2.0-3.0), balancing bleeding complications with under-dosing and stroke-risk. 16 Dietary and drug interactions which affect INR, frequent INR-monitoring, and perceptions of warfarin as 'rat poison' add to greater perceived disease burden and may contribute to non-adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of AF, higher personal control beliefs may be reflective of beliefs that AF is cyclic and that repeated behavioural and lifestyle modifications, reflected by high scores for this group on health-behaviour triggers, can prevent AF symptoms. This is supported by a recent qualitative study where patients who reported a perceived lack of understanding of AF, also tended to speak about increased monitoring of AF and control attempts, leading to increased emotional distress [37].…”
Section: Discussionmentioning
confidence: 61%
“…Several qualitative studies have focused on the patient with AF [12][13][14]. Quantitative studies have also shown how patients with AF struggle with impaired health-related quality of life, stress and anxiety due to AF symptoms [15].…”
Section: Introduction/backgroundmentioning
confidence: 99%